Impact of smart city construction policy on high-quality economic development of coastal cities - Lihong Wang; Lihong Wang; Feng Li; Yang Gao; Kedong Yin (Frontiers in Marine Science)
IntroductionAs a crucial strategy for promoting urbanization in China, smart city construction introduces new momentum for high-quality economic development through intelligence and informatization. Coastal cities, with their unique geographical and economic advantages, serve as important engines of high-quality economic growth.MethodsBased on panel data from 53 coastal cities in China from 2003 to 2021, this study uses the super-efficiency SBM-GML index to measure green total factor productivity as an indicator of high-quality economic development and employs a time-varying difference-in-differences model to examine the impact of smart city construction on high-quality economic development in coastal areas.ResultsThe findings reveal that (1) Smart city construction significantly enhances high-quality economic development in coastal cities. This conclusion remains valid in parallel trend tests, PSM-DID, placebo tests and endogeneity analysis. (2) The mechanism test shows that smart city construction development primarily promotes high-quality economic growth in coastal cities by facilitating industrial structural upgrading, optimizing resource allocation, and release household consumption potential and expanding domestic demand. However, technological innovation, which is the most important aspect of smart city construction, has not brought new opportunities for high-quality economic development in coastal cities. (3) Heterogeneity analysis shows that the policy effects of smart city are more pronounced in large cities and those with lower levels of scientific and educational development. Additionally, the impact is particularly significant in cities located within the Bohai Rim and Yangtze River Delta port clusters.DiscussionBased on these findings, continued support for smart city construction is recommended, with differentiated policies tailored to the characteristics of coastal cities and port cluster development levels, alongside advancing industrial structural upgrading, optimizing resource allocation, and fostering new points of consumption growth to promote high-quality economic development in China’s coastal cities.